1993
DOI: 10.1099/00221287-139-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the expression of a pelA:: uidA fusion in Erwinia chrysanthemi and demonstration of the synergistic action of plant extract with polygalacturonate on pectate lyase synthesis

Abstract: The phytopathogenicity of Erwinia chrysanthemi is chiefly supported by the production of pectate lyase isoenzymes, encoded by the pel genes. One of these enzymes, PelA, encoded by the pelA gene, seems to represent only a small part of the total pectate lyase activity, but is required for full bacterial pathogenicity. To study the regulation of pelA gene expression, a pelA::uidA gene fusion was constructed. Expression of this fusion was analysed under various growth conditions and in various genetic backgrounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…on May 8, 2018 by guest http://jb.asm.org/ called hyperinduction, but the inducers were not identified (3,14,25). The presence of ferulic acid results in the same type of hyperinduction.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…on May 8, 2018 by guest http://jb.asm.org/ called hyperinduction, but the inducers were not identified (3,14,25). The presence of ferulic acid results in the same type of hyperinduction.…”
mentioning
confidence: 79%
“…For this induction, ferulic acid acts in synergy with the pectate lyase substrate polygalacturonate (Table 3), which when cleaved, liberates strong inducers (13). Such synergy has been previously observed with crude plant extracts (3,25), and it is probably due to the effect of several plant compounds, including ferulic acid. It was recently shown that some phenolic compounds affect the expression of the type III secretion system of D. dadantii.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…E. chrysanthemi 3937 synthesizes five major endo pectate lyases, encoded by pelA to pelE (39), and a set of minor ones. Transcription of the pel genes is induced by pectin catabolic products, the stationary growth phase, host plant metabolites (7), and iron depletion (28). Transcription of these genes is repressed by nitrogen starvation, high temperature, and high osmolarity and is under catabolic repression (16).…”
mentioning
confidence: 99%
“…In addition, the transcription of pectate lyase genes is subject to other physiological controls, including growth phasedependent induction (14), catabolite repression, and regulation by environmental conditions such as anaerobiosis, osmolarity, temperature, iron and nitrogen starvation, or the presence of plant extracts (5,13,40).…”
mentioning
confidence: 99%